Pengaruh Perbedaan Waktu Fermentasi Probiotik (Lactobacillus sp) yang Berbeda pada Pakan Buatan terhadap Pertumbuhan Berat Mutlak Udang Vannamei (Litopenaeus vannamei) DOC 80 di Bak Pemeliharaan - Oktovandiansyach Tegar Imanan; Didik Budiyanto; Sumaryam Sumaryam (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2025)
The addition of probiotics such as Lactobacillus sp to fermented feed is expected to improve nutrient digestibility, suppress the growth of pathogenic microorganisms, and improve feed conversion efficiency, thereby promoting optimal shrimp growth. This study used an experimental method on vannamei shrimp doc 80 using a complete randomized design (RAL) with four treatments: P0 (feed without fermentation as a control), P1 (feed fermentation for 0 hours 10ml/100g with Lactobacillus sp), P2 (feed fermentation for 24 hours with 10ml/100g Lactobacillus sp), P3 (feed fermentation for 48 hours 10ml/100g Lactobacillus sp), P3 (feed fermentation for 72 hours 10ml/100g Lactobacillus sp) by doing 6 repetitions which were carried out for 1 month/30 days in the maintenance tub. The results showed that Treatment A without fermentation gave absolute growth with an average of 1 gr, Treatment B with no fermentation gave absolute growth with an average of 1.89 grams, Treatment C with a fermentation time of 48 hours gave absolute weight growth with an average of 2.15 grams, Treatment D with no fermentation gave absolute growth with an average of 0.74 grams. Meanwhile, the water quality parameters during the study were obtained with water temperature ranging from 28.3-29.6o C, pH ranging from 7.8-8.0, and dissolved oxygen ranging from 4.03-4.66 mg/l. With the anova test, the absolute weight growth showed that with different fermentation time differences, there was a real effect on the growth of vannamei shrimp in C treatment, which was 2.15 gr. And in the results of the anova test, the four water quality parameters were not different between the treatments and were in the optimal range in the life of vannamei shrimp. Based on this study, it can be suggested that the optimal fermented feed is in the time range of 48 hours and there is further research for doc 80 and above.